Combinational therapy, concomitantly targeting post‐translational modified Aβ peptides and CD33, leads to an add‐on effect in passive immunotherapy. (31st December 2021) - Gnoth, Kathrin; Geissler, Stefanie; Ilse, Victoria; Rahfeld, Jens‐Ulrich; Cynis, Holger; Schilling, Stephan
Abstract: Background: Passive immunotherapy is a very promising approach for the treatment of Alzheimer's disease (AD). We recently demonstrated that the antibody‐mediated targeting of isoD7‐modified Aβ peptides leads to the attenuation of AD‐like amyloid pathology in 5xFAD mice (Gnoth et al., 2020). Targeting post‐translationally modified Aβ peptides is a promising approach for reduction of effective therapeutic antibody amount and thereby decreasing treatment‐related side effects. Nevertheless, high dosing of monoclonal antibodies and appearance of side effects such as amyloid‐related imaging abnormalities (ARIAs) provide room for approaches such as combination therapies. Method: We investigated the role of CD33 for Aβ phagocytosis in transgenic mice treated with an isoD7‐Aβ antibody. CD33 or sialic‐acid‐binding immunoglobulin‐like lectin 3 (Siglec‐3) is an inhibitory receptor molecule on the surface of brain microglia. We generated a new mouse line by crossing 5xFAD mice (Oakley et al., 2006) with CD33 knock out mice (Brinkman‐Van der Linden et al., 2003). This mouse line was then used for treatment studies with our anti‐isoD7‐Aβ antibody K11_IgG2a. Therefore, 3month‐old female 5xFAD and 5xFAD/CD33 mice were treated with 4 mg/kg K11_IgG2a and IgG2a isotype control. After 38 weeks treatment an Elevated Plus Maze (EPM) test have been performed, followed by the preparation of mouse brain and the read out by ELISA and Immunohistochemistry. Result: We could demonstrate that CD33 knock out leads to the reduction of Aβ plaque load as well as the rescue of behavioral deficits in 5xFAD mice. Above that, we detected elevated amounts of plaque surrounding microglia in 5xFAD/CD33KO mice receiving antibody treatment, followed by an even more decrease of Aβ plaque load. Conclusion: In summary, a combinational therapy, concomitantly targeting post‐translational modified Aβ peptides and CD33, leads to an add‐on effect in passive immunotherapy.